Direct platelet adhesion potentiates group 2 innate lymphoid cell functions. Issue 3 (24th August 2021) - Orimo, Keisuke; Tamari, Masato; Takeda, Tomohiro; Kubo, Terufumi; Rückert, Beate; Motomura, Kenichiro; Sugiyama, Hiroki; Yamada, Ayako; Saito, Kyoko; Arae, Ken; Kuriyama, Motohiro; Hara, Mariko; et al.
Abstract: Background: Platelets are thought to be involved in the pathophysiology of asthma, presumably through direct adhesion to inflammatory cells, including group 2 innate lymphoid cells (ILC2s). Here, we tried to elucidate the effects of platelet adhesion to ILC2s in vitro and in vivo, as well as the mechanisms involved. Methods: Alternaria ‐induced ILC2‐dependent airway inflammation models using wild‐type and c ‐ mpl −/− mice were evaluated. Both purified CD41 + and CD41 − ILC2s were cultured with IL‐2 and IL‐33 to determine in vitro Type 2 (T2) cytokine production and cell proliferation. RNA‐seq data of flow‐cytometry‐sorted CD41 + and CD41 − ILC2s were used to isolate ILC2‐specific genes. Flow cytometry was performed to determine the expression of CD41 and adhesion‐related molecules on ILC2s in both mouse and human tissues. Results: T2 inflammation and T2 cytokine production from ILC2s were significantly reduced in the c ‐ mpl −/− mice compared to wild‐type mice. Platelet‐adherent ILC2s underwent significant proliferation and showed enhanced T2 cytokine production when exposed to IL‐2 and IL‐33. The functions of ILC2‐specific genes were related to cell development and function. Upstream regulator analysis identified 15 molecules, that are thought to be involved in ILC2 activation. CD41 expression levels were higher in ILC2s from human PBMCs and mouse lung than in those from secondary lymphoid tissues, but they did not correlate with the P‐selectin glycoprotein ligand‐1 or CD24 expression level. Conclusion: Platelets spontaneously adhere to ILC2s, probably in the peripheral blood and airways, thereby potentiating ILC2s to enhance their responses to IL‐33. Abstract : Lung ILC2s from platelet‐deficient mice have less capacity to produce T2 cytokines than WT mice, which results in attenuation of ILC2‐dependent eosinophilic airway inflammation in those mice. The degree of platelet adhesion to ILC2s varies depending on the organ in both mice and humans. Platelet–adherent ILC2s show enhanced proliferation and T2 cytokine production compared with non–platelet–adherent ILC2s. Abbreviations: FALC, fat‐associated lymphoid cluster; ILC2, group 2 innate lymphoid cell; T2, type–2